SOCIAL VULNERABILITY ANALYSIS IN THE IMPLEMENTATION OF COMPLETE SYSTEMATIC LAND REGISTRATION - COMMUNITY PARTICIPATION IN THE AGRARIAN REFORM ACCELERATION PROGRAM IN GUGUK AND BENTENG VILLAGES, MERANGIN REGENCY - Hamzah; Widiyanto, Petrus; Napitupulu, Richard R.P.; Fitri, Yanuar (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2024)
This study analyzes social vulnerability in implementingComplete Systematic Land Registration (PTSL) and community participation in the Agrarian Reform Acceleration Program (PPRA) in Guguk Village and Benteng Village, Merangin Regency. The main problem of land governance in Indonesia is the unclear boundaries of land areas that lead to tenurial conflicts and weak protection of land rights, especially for indigenous peoples and farmers. Since 2010, the Government of the Republic of Indonesia has implemented the One Map Policy which seeks to provide integrated geospatial data on land use and natural resources for policy-making processes at the national and regional levels. In line with this, the Government of Indonesia also implements the Agrarian Reform Program. The Ministry of Agrarian Affairs and Spatial Planning/National Land Agency in the 2015-2019 RPJM is responsible for issuing 23 million land certificates (4.1 million hectares) outside forest areas (Other Use Areas - APL) through the village-based Complete Systematic Land Registration (PTSL). The PTSL program is very important to strengthen land ownership, but it also carries a high risk of triggering social conflict, especially in the context of social vulnerability that impacts vulnerable groups. This study emphasizes the need to understand the social and environmental risks arising from the program and its impacts on communities, especially related to conflicts over access and land ownership